PENERAPAN METODE ROLE PLAYING BERBANTUAN MEDIA MATH SHOP UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BILANGAN CACAH DI KELAS IV SD NEGERI 6 GANDAPURA - Jihanul Hawada; Mislinawati; Linda Vitoria (STKIP Subang, 2026)
This research is motivated by the low understanding of fourth-grade elementary school students on the material of whole numbers caused by a learning approach that is not yet in accordance with students' cognitive development. The application of the Role Playing method assisted by Math Shop media is seen as being able to bridge the gap through real contexts and meaningful activities. This study aims to determine the learning outcomes of fourth-grade students of SD Negeri 6 on the material of whole numbers. The study used a qualitative approach with a Classroom Action Research (CAR) design for 24 students. Data were collected through observations of teacher activities, observations of student activities and student learning outcome tests after learning, then analyzed using the average value of observation scores in each cycle to determine the level of learning implementation. Thus, the application of the Role Playing method assisted by Math Shop media can improve student learning outcomes on the material of whole numbers, although it requires time management in several cycles.